Introducing the bio‐psycho‐social‐physical model of dementia through a collective case study design. Issue 19 (24th September 2012) - Keady, John; Jones, Lesley; Ward, Richard; Koch, Susan; Swarbrick, Caroline; Hellström, Ingrid; Davies‐Quarrell, Vivienne; Williams, Sion
Abstract : Aims and objectives: To provide evidence for the development of a physical domain attached to the well‐known bio‐psycho‐social model of dementia. The objectives were to develop a set of international case studies that followed a trajectory approach, from prevention to end‐of‐life care. Background: In the UK the bio‐psycho‐social model has informed the shape of the National Institute for Health and Clinical Excellence and the Social Care Institute for Excellence 'dementia' guideline. However, limited attention has been paid to outlining and describing a physical domain of dementia, a discrepancy that informed the rationale for this study. Design: A collective case study design was used to address the research aim and objectives. Methods: Case studies from along the trajectory of dementia were provided by an international team of contributors from an inter‐disciplinary background comprising nursing (general and mental health), social work and social science. Results: The team's synthesis and analysis of the six case studies generated five repeating themes with each theme becoming components of a 'physical' domain of dementia. The five identified physical components were: (1) physical well‐being, (2) physical health and examination, (3) physical care, (4) physical treatment and (5) physical environment. Conclusions: The development of a bio‐psycho‐social‐physical model of dementia presents a holistic and culturally sensitive approach to understanding the experience of living with dementia, and to providing care and support in a variety of situations and contexts. Relevance to clinical practice: The physical domain of dementia has particular relevance to nursing and nursing practice, such as providing physical care at the end‐of‐life. The interplay between the biological‐psychological‐social‐physical domains of dementia and the trajectory of dementia could form the basis of clinical decision‐making and practice.